2014
DOI: 10.1126/scitranslmed.3008810
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of heterotopic ossification through remote ATP hydrolysis

Abstract: Heterotopic ossification (HO) is the pathologic development of ectopic bone in soft tissues because of a local or systemic inflammatory insult, such as burn injury or trauma. In HO, mesenchymal stem cells (MSCs) are inappropriately activated to undergo osteogenic differentiation. Through the correlation of in vitro assays and in vivo studies (dorsal scald burn with Achilles tenotomy), we have shown that burn injury enhances the osteogenic potential of MSCs and causes ectopic endochondral heterotopic bone forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
139
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(143 citation statements)
references
References 33 publications
2
139
0
2
Order By: Relevance
“…Mesenchymal cells with the capacity for osteogenic differentiation and which may serve as HO progenitor cells reside within adipose tissues, making this an appropriate tissue type to assay. Additionally, burn patients are a critical patient population at risk for trauma-induced HO development (2,3,20). Our recent analysis has shown that patients with burn total body surface area (TBSA) > 30% have 23-times higher odds of developing HO compared with patients with smaller surface-area burns, validating use of this cohort of patients with >20% TBSA burns for transcriptome analysis (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mesenchymal cells with the capacity for osteogenic differentiation and which may serve as HO progenitor cells reside within adipose tissues, making this an appropriate tissue type to assay. Additionally, burn patients are a critical patient population at risk for trauma-induced HO development (2,3,20). Our recent analysis has shown that patients with burn total body surface area (TBSA) > 30% have 23-times higher odds of developing HO compared with patients with smaller surface-area burns, validating use of this cohort of patients with >20% TBSA burns for transcriptome analysis (21).…”
Section: Discussionmentioning
confidence: 99%
“…This process occurs in two separate patient populations: those with severe trauma, including large surface-area burns, musculoskeletal injury, orthopedic operations, and even spinal cord injury; and those with a genetic disease known as fibrodysplasia ossificans progressiva (FOP) (1)(2)(3)(4). FOP is caused by a hyperactivating mutation in the type I bone morphogenetic protein (BMP) receptor ACVR1 (Activin type 1 receptor), and patients with FOP develop ectopic bone lesions in the absence of any substantial trauma.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Peterson et al [19] demonstrated in a murine Achilles tenotomy plus partial-thickness dorsum burn injury model that injured mice develop endochondral ectopic bone and functional joint contractures through BMP-mediated canonical small ''mothers against'' decapentaplegic (SMAD) signaling. Moreover, they report that these orthopaedic disease processes can be attenuated/modulated by targeting adenosine triphosphate (ATP) hydrolysis and SMAD1/5/8 phosphorylation at the burn site using apyrase [19].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they report that these orthopaedic disease processes can be attenuated/modulated by targeting adenosine triphosphate (ATP) hydrolysis and SMAD1/5/8 phosphorylation at the burn site using apyrase [19]. Interestingly, it has been reported that focused extracorporeal shockwave therapy (ESWT; low-density shockwaves administered orders of magnitude below blast overpressure conditions used in the study) has been shown to induce osteogenic differentiation of marrow-derived mesenchymal stem cells through ATP release and downstream transcriptional signaling events resulting in activation of P2X7 receptors [28].…”
Section: Discussionmentioning
confidence: 99%